2011
DOI: 10.1038/aps.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of REST corepressor 3 in prognosis of human hepatitis B

Abstract: Aim: To examine the potential correlation between serum REST corepressor 3 (RCOR3) level and the outcome of patients with hepatitis B. Methods: Concanavalin A (ConA)-induced mouse hepatitis model was used. The mRNA level of RCOR3 in mouse liver was measured using GeneChip array and real-time PCR. One hundred seventy-seven patients with hepatitis B and 34 healthy individuals were categorized into six groups including mild chronic hepatitis, moderate chronic hepatitis B, severe hepatitis B (SHB), cirrhosis, hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…While the incomplete expression profile of Rcor2 makes it difficult to predict the extent and severity of its genetic deletion phenotype, the Rcor1 and Rcor2 combined deletions should largely phenocopy that of LSD1 in the absence of other positively acting Rcor factors. Since very little is known about Rcor3 expression or function other than its expression in adult hepatic cells (28), predicting its deletion phenotype is practically impossible. However, our results predict antagonistic phenotypes for Rcor 1/2 versus Rcor3 in their respective regions of expression.…”
Section: Discussionmentioning
confidence: 99%
“…While the incomplete expression profile of Rcor2 makes it difficult to predict the extent and severity of its genetic deletion phenotype, the Rcor1 and Rcor2 combined deletions should largely phenocopy that of LSD1 in the absence of other positively acting Rcor factors. Since very little is known about Rcor3 expression or function other than its expression in adult hepatic cells (28), predicting its deletion phenotype is practically impossible. However, our results predict antagonistic phenotypes for Rcor 1/2 versus Rcor3 in their respective regions of expression.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid bias, we mined expression data for all four genes. We found that RCOR3, CYTL1 and E2F8 are not expressed appreciably in neuronal tissues, while subsequent literature searches intimate an involvement of these transcripts in hepatitis, chondrogenesis and hepatocellular carcinoma (3,23,24). In contrast, TENM4 is expressed primarily in the brain and has been detected in several transcriptomes derived from neuronal tissues (see Materials and Methods).…”
Section: Exome Sequencingmentioning
confidence: 91%
“…[327] Xu et al found that verapamil increased β-AR density and inhibited norepinephrine-induced β-AR downregulation of cardiomyocytes. [328] Staneva-Stoytcheva et al studied the influence of long-term treatment with verapamil, on β-adrenoceptors in rat cerebral cortex. They found that 13-day treatment of rats with verapamil significantly reduced (by about 30%) the number (B max ) of β-adrenoceptors.…”
Section: Verapamil Potassium Channels Blockingmentioning
confidence: 99%